Postorogenic rigid behavior of the eastern Songpan‐Ganze terrane: Insights from low‐temperature thermochronology and implications for intracontinental deformation in central Asia. (26th February 2014) - Tian, Yuntao; Kohn, Barry P.; Hu, Shengbiao; Gleadow, Andrew J. W.
<x xml:space="preserve">Abstract</x> [1] The Songpan‐Ganze terrane (SGT), formed by Early Mesozoic closure of the Paleo‐Tethys Ocean, occupies a large area of the central‐eastern Tibetan Plateau. Late Mesozoic and Cenozoic strike‐slip deformation has been identified in the surrounding terranes and faults (e.g., western Qinling, Altyn Tagh, and Kunlun faults); however, the coeval evolution of the SGT has not been well explored. We report apatite fission track and apatite and zircon (U‐Th)/He data from a >7 km deep borehole and outcrop samples covering an area of >150 × 150 km in the eastern SGT. Thermal history modeling suggests a distinct phase of Late Jurassic‐Early Cretaceous (∼150–100 Ma) cooling, followed by a prolonged stage of slow cooling, for all samples despite of their differences in depositional age (Mid‐Late Triassic time) and locality within a large area. The ubiquitous Late Jurassic‐Early Cretaceous cooling implies little differential deformation in the eastern SGT and is best explained by regional rock uplift resulting from the transpressional strain field created by the contemporaneous Lhasa‐Qiangtang collision to the south. Projecting the contemporaneous deformation surrounding the SGT onto an Early Cretaceous paleogeographic terrane reconstruction results in a new tectonic model. The model relates the Lhasa‐Qiangtang collision to tens to hundreds of kilometers of shearing along the Altyn Tagh and Kunlun faults, which transferred strain into central Asia (e.g., Qinling‐Dabie orogen). Results of this study suggest a rigid behavior for the eastern SGT and highlight the important role of crustal strength discontinuities in accommodating and transferring crustal deformation.